Limitations of macroscopic fluorescence imaging for the estimation of tumour growth in an orthotopic glioma mouse model - Hilšer, Marek; Trylčová, Jana; Bušek, Petr; Šedo, Aleksi (Folia biologica (Praha), 2012)
Imaging methods based on light detection are being increasingly used for the non-invasive assessment of tumour growth in animal models. In contrast with bioluminescence imaging, there are no studies assessing the use of macroscopic fluorescence imaging for the longitudinal monitoring of tumour growth in an orthotopic glioma mouse model. Glioma cells expressing the red-shifted fluorescent protein mKate2 were orthotopically implanted to NOD-rag mice and the tumour size estimated by macroscopic fluorescence imaging was compared to the tumour volume determined morphometrically. There was no significant correlation between the data obtained by non-invasive macroscopic fluorescence imaging and post mortem morphometry. In addition, the fluorescence imaging failed to detect a morphometrically verified difference in tumour volume between animals with tumours expressing a potential tumour suppressor gene and controls. The fluorescence signal was affected by the spatial pattern of tumour growth and substantially attenuated by the interfering brain tissue. Our results indicate that the fluorescence signal emitted by glioma cells reflected not only the tumour mass, but also its spatial distribution. Macroscopic planar FLI in an epi-illumination mode and a conventional source of excitation light therefore appears to be more suitable for semi-quantitative assessment of the tumour growth especially in the case of superficially located tumours rather than for precise volume estimation of the xenografts located deep within the brain tissue.
Keywords: Humans; Tomography, Optical; lidé; Diagnostic Imaging; zvířata; myši; Fluorescence; Mice; optická tomografie; Male; Neoplasm Transplantation; transplantace nádorů; gliom; nádorové buněčné linie; fluorescence; Animals; diagnostické zobrazování; Cell Line, Tumor; mužské pohlaví; Disease Models, Animal; Glioma; modely nemocí na zvířatech